ADAPTASI FONOLOGIS DAN SEMANTIS KATA SANSKERTA DALAM BAHASA JAWA - Hasan Ashari; Fiska Amanda Mulia (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
This study examines the adaptation of Sanskrit lexicons in the Javanese language, a process persisting since the 4th century CE as an instrument of religion, literature, and political authority. The primary focus is to identify systematic patterns of phonological change and semantic shifts that facilitated the integration of this foreign language into the local system. Employing a qualitative descriptive approach within a historical linguistic perspective, data analysis was conducted through etymological tracing of Old and Modern Javanese text corpora, phonotactic classification to map sound transformations, and synchronic diachronic analysis to detect semantic evolution. The findings reveal that phonological adaptation occurred through deaspiration and consonant cluster simplification to satisfy Javanese phonological constraints. Semantically, a “nativization” of meaning took place through mechanisms of narrowing, widening, and recontextualization aligned with the community's sociocultural reality. These findings affirm that the Javanese language functions as an active filter that nativizes Sanskrit elements, rendering them an integral part of the Nusantara linguistic identity that remains adaptive to this day.